Pregnancy Outcomes of Women Conceiving on Antiretroviral Therapy (ART) Compared to Those Commenced on ART During Pregnancy. (20th June 2020) - Theron, Gerhard; Brummel, Sean; Fairlie, Lee; Pinilla, Mauricio; McCarthy, Katie; Owor, Maxensia; Chinula, Lameck; Makanani, Bonus; Violari, Avy; Moodley, Dhayendre; Chakhtoura, Nahida; Browning, Renee; et al.
Abstract: Background: Globally, the number of infected women of childbearing age living with human immunodeficiency virus (HIV) and conceiving on antiretroviral therapy (ART) is increasing. Evidence of ART safety at conception and during pregnancy and adverse pregnancy outcomes remains conflicting. The Promoting Maternal and Infant Survival Everywhere (PROMISE) 1077 breastfeeding (BF) and formula feeding (FF) international multisite trials provide an opportunity to examine the impact of ART at conception on pregnancy outcomes with subsequent pregnancies. Methods: The PROMISE 1077BF/1077FF trials were designed to address key questions in the management of HIV-infected women who did not meet clinical guidelines for ART treatment during the time of the trials. After the period of risk of mother-to-child transmission was over, women were randomized to either continue or discontinue ART. We compared subsequent pregnancy outcomes of nonbreastfeeding women randomized to continue ART following delivery, or breastfeeding women randomized to continue ART following breastfeeding cessation who conceived while on ART to women randomized to discontinue ART, who restarted ART after pregnancy was diagnosed. Results: Pregnancy outcomes of 939 subsequent pregnancies of 826 mothers were recorded. The intention-to-treat analyses showed increased incidence of low birth weight (<2500 g) for women who conceived while on ART (relative risk, 2.65 [95% confidence interval CI, 1.20–5.81]), and also a higher risk of spontaneous abortion, stillbirth, or neonatal death (hazard ratio, 1.40 [95% CI, .99–1.98]) compared to women who restarted ART after they were found to be pregnant during trial follow-up. Conclusions: We found an increased risk for adverse pregnancy outcomes in women conceiving on ART, emphasizing the need for improved obstetric and neonatal care for this group. Clinical Trials Registration: NCT01061151. Abstract : Globally more women living with HIV conceive on antiretroviral therapy (ART). This study reports an increased risk of low birth weight, spontaneous abortion, stillbirth, and neonatal death for women conceiving on ART compared to those not on ART at conception.